Pre-trial protocol in civil proceedings: issues of effectiveness in practice - Nurekeshov, T.K.; Aytkazin, Y.M. (Bulletin of the Karaganda University “Law Series”, 2024)
The scientific article analyzes the change of legislation in the form of introduction of pre-trial protocol to civil proceedings by Law No. 84-VII of the Republic of Kazakhstan dated December 20, 2021. According to the innovation, this procedure is carried out by mutual exchange of the parties pre-trial protocol or with the help of a conciliation judge. The conciliation judge is not a party to the substantive dispute, but ensures the exchange of evidence between the parties in case of submission of the pre-trial protocol and evidence. The authors believe that today it is time to make the first conclusions about the effectiveness of the application of the pre-trial protocol in practice. The authors also see the relevance of the research topic in the functioning of this object of study as a means of resolving pre-trial disputes. Therefore, this article attempts to assess the practical effectiveness of the research object on the basis of statistical data, by analyzing the norms providing for the application of pre-trial protocol in Kazakhstani legislation and reviewing the opinions of research scientists and specialists in this field. That is, the purpose of the research is to study and assess the practical effectiveness of the pre-trial protocol. Practice shows that the number of disputes resolved using this tool is too small and, according to the authors, the legislator has not yet achieved the goal of introducing a pre-trial protocol. In their opinion, there are enough barriers to the full-fledged operation of this innovation.